Promise and limitations of 18S genetic screening of extracted fecal DNA from wild capuchins - Pinto, Swellan Luciann; Henriquez, Megan Carvalho; Cheves Hernandez, Saul; Duytschaever, Gwen; Wit, Janneke; Avramenko, Russell William; Gilleard, John Stuart; Orkin, Joseph Daniel; Melin, Amanda Dawn (Frontiers in Ecology and Evolution, 2023)
Genomic screening of fecal DNA provides insight into diet, parasite infection dynamics, and other aspects of the ecology and pathogens of wild populations. Here, we amplify and sequence the V4/V5 regions of the eukaryotic 18S ribosomal RNA gene from fecal DNA of wild capuchin monkeys (Cebus imitator). We collected 94 fecal samples from 26 individuals, each sampled 1-4 times across a 19-month period and examined the eukaryotic diversity in 63 of these samples which had sufficient numbers and quality of reads during downstream analyses. We found a total of 234 distinct amplicon sequence variants (ASVs) classified as Eukaryotes in our samples. Of these, 66 were assigned to the phylum Nematoda. 64 ASVs are from taxa that possibly parasitize monkeys or their food items: 33 were assigned to lungworms (Superfamily Metastrongyloidae; genus Angiostrongylus), two to the genus Strongyloides, and one to the genus Austrostrongylus. The remaining 28 ASVs were assigned to nematodes that likely parasitize plants and/or invertebrates that the monkeys consume. Taken together with past dietary and coprological study of the same primate population, our results suggest that invertebrate consumption and parasitic infection, especially by lungworms, is common and widespread among this population of wild monkeys. We also discuss limitations of our approach, including the amplification of off-target ASVs, and make suggestions for future research. Overall, 18S screening shows promise for identifying various components of the capuchin gastrointestinal eukaryotic ecosystem, including parasitic helminths, and its utility will increase with the improvement of genetic databases.